1994
DOI: 10.1177/0013161x94030002003
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion in Secondary Schools: An Analysis of School Structure Based on Teachers' Images of Change

Abstract: The practice of providing totally inclusive schools to meet the needs of all learners is one of the emerging service delivery options gaining widespread support in public education in Canada and the United States. While many elementary schools have taken the initiative and established successful models of full inclusion, secondary schools, in part because of the historical-structural characteristics of these organizations, embody different and perhaps more complex problems in meeting the demands of inclusive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…In such schools, the formal authority of principals might decrease in importance as educators work within uncertain role definitions and engage in more collaborative practices (Mintzberg, 1979). Empirical research validates Skrtic's assertion that more adhocratic school structures emerge in the successful implementation of inclusion (MacKinnon & Brown, 1994).…”
mentioning
confidence: 61%
“…In such schools, the formal authority of principals might decrease in importance as educators work within uncertain role definitions and engage in more collaborative practices (Mintzberg, 1979). Empirical research validates Skrtic's assertion that more adhocratic school structures emerge in the successful implementation of inclusion (MacKinnon & Brown, 1994).…”
mentioning
confidence: 61%
“…In some ways the Connolly School resembled Skrtic & Sailor' s (1996) postmodern``adhocracy' ' in which each member of the community collaborates in decision making, creating a high level of interdependence. MacKinnon and Brown (1994) argue that structure of an adhocracy with its emphasis on team building, collaborative decision making and ability to adapt to changing circumstances is more conducive to an inclusive educational model than the traditional, bureaucratic school structure with its emphasis on standardization and hierarchy. They argue that restructuring schools to resemble adhocracies rather than bureaucracies can contribute to the success of inclusion.…”
Section: A Democratic Approachmentioning
confidence: 99%
“…Inclusion arguably requires democracy and openness to be successful (MacKinnon & Brown, 1994 ;Perner, 1991). Implementing an inclusion program is diae cult and even anxious work that can result in feelings of vulnerability as broad changes are instituted and comfortable practices and structures are dismantled.…”
Section: A Democratic Approachmentioning
confidence: 99%
“…It was undertaken to broaden the application of Galis' survey instrument by studying a special database (Galis, 1994;Galis & Tanner, 1995). MacKinnon and Brown (1994) reported that secondary schools "in part because of the historical-structural characteristics of these organizations, embody different and perhaps more complex problems [than elementary schools] in meeting the demands of inclusive educational practices" (p. 126). Anderman and Maehr (1994) argued that student motivation differed in middle school from elementary school settings.…”
Section: Purpose Of the Studymentioning
confidence: 99%